Changes in liver and L-cell plasma membranes during infection with Coxiella burnetii. - Marecki, N (1978)
Changes in plasma membrane proteins of guinea pig liver and L-929 cells were studied during infection with Coxiella burnetii. Polypeptide species resolved by disc polyacrylamide gel electrophoresis with sodium dodecyl sulfate showed quantitative but no qualitative differences between uninfected and infected samples. When the O'Farrell technique of isoelectric focusing, followed by sodium dodecyl sulfate-slab gel polyacrylamide gel electrophoresis, was employed, additional polypeptides were resolved. Livers and L cells were labeled with [3H]-glucosamine. Infected livers incorporated less [3H]glucosamine in the membrane proteins than uninfected material, presumably indicating lower glycoprotein levels. Infected L-cell membranes incorporated greater amounts of [3H]glucosamine, and also were labeled to a greater extent than uninfected membranes, employing the [125I]lactoperoxidase technique. Uninfected L cells showed a greater agglutinability with concanavalin A than did infected cells. Infected livers had much greater levels of cyclic adenosine 3',5'-monophosphate. The data indicate changes in plasma membranes as a result of infection. Possible physiological consequences of membrane changes are discussed.